2012
DOI: 10.3390/molecules18010263
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Functional Analyses Reveal MAPK1 Regulates Milk Protein Synthesis

Abstract: L-Lysine (L-Lys) is an essential amino acid that plays fundamental roles in protein synthesis. Many nuclear phosphorylated proteins such as Stat5 and mTOR regulate milk protein synthesis. However, the details of milk protein synthesis control at the transcript and translational levels are not well known. In this current study, a two-dimensional gel electrophoresis (2-DE)/MS-based proteomic technology was used to identify phosphoproteins responsible for milk protein synthesis in dairy cow mammary epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Expression of β-CN may have a compensation effect between the variants. The in vitro bovine mammary epithelial cell results indicated that not only did the cells grow but β-CN expression was also promoted with the addition of Lys to the media (Lu et al, 2013). Based on our findings, we hypothesize that concentrations of essential AAs, such as Lys, are higher in mammary gland cells because they can be supplemented by microbial protein in dairy cows fed SSBM, which displays a higher rumen degradable protein than HSBM.…”
Section: Caseinsmentioning
confidence: 68%
“…Expression of β-CN may have a compensation effect between the variants. The in vitro bovine mammary epithelial cell results indicated that not only did the cells grow but β-CN expression was also promoted with the addition of Lys to the media (Lu et al, 2013). Based on our findings, we hypothesize that concentrations of essential AAs, such as Lys, are higher in mammary gland cells because they can be supplemented by microbial protein in dairy cows fed SSBM, which displays a higher rumen degradable protein than HSBM.…”
Section: Caseinsmentioning
confidence: 68%
“…To determine the effect of methionine (Met) on 14-3-3c, eIF1AX and RPS7 expression in BMECs, cells were treated with Met (0.6 mmol L À1 ) for 24 h as in our previous study [22]. Western blot and immunofluorescence analysis showed that 14-3-3c, eIF1AX and RPS7 were overexpressed after Met stimulation in BMECs ( Fig.…”
Section: The Proteins 14-3-3c Interacts With In Bmecsmentioning
confidence: 99%
“…We carried out western blot analysis in the same way as previously reported [22]. Primary antibodies used in this work were: 14-3-3c (1:6000, Abcam, ab 79165, MA, USA), eIF1AX Densitometric analysis of the immunoreactive bands was performed using the ImageJ program (US National Institutes of Health, MA, USA).…”
Section: Western Blotmentioning
confidence: 99%
“…Leu affects translation by enhancing mTOR activity indirectly and the translation initiation complex directly. Lys appears to augment translation through the phosphorylation of Mitogen-activated Protein Kinase that in turn enhances the expression and phosphorylation of mTOR and STAT5a, as recently demonstrated in bovine mammary cells (133). Met is well known for its essential role in the initiation of mRNA translation, which is the binding of methionyl-tRNA to the 40S ribosomal subunit followed by the joining of a 60S ribosomal subunit to form a translationally competent 80S ribosome (112).…”
Section: Aa Effect On Transcription Of Milk Protein Synthesis-relatedmentioning
confidence: 99%